2005
DOI: 10.1103/physrevlett.94.202002
|View full text |Cite
|
Sign up to set email alerts
|

First Measurement of the Transverse Spin Asymmetries of the Deuteron in Semi-inclusive Deep Inelastic Scattering

Abstract: First measurements of the Collins and Sivers asymmetries of charged hadrons produced in deep-inelastic scattering of muons on a transversely polarized 6LiD target are presented. The data were taken in 2002 with the COMPASS spectrometer using the muon beam of the CERN SPS at 160 GeV/c. The Collins asymmetry turns out to be compatible with zero, as does the measured Sivers asymmetry within the present statistical errors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(91 citation statements)
references
References 26 publications
7
83
0
1
Order By: Relevance
“…The next step is to complete this program. Then we will apply the LF spectral function to other processes (e.g., DVCS) to exploit other possibilities to use 3 He as an effective neutron target and as a laboratory for light-front studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The next step is to complete this program. Then we will apply the LF spectral function to other processes (e.g., DVCS) to exploit other possibilities to use 3 He as an effective neutron target and as a laboratory for light-front studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamical nuclear effects in inclusive deep inelastic electron scattering (DIS) 3 He(e, e ′ )X (DIS) were evaluated [6] with a realistic 3 He spin-dependent spectral function, P τ σ,σ′ (p, E, S He ), with p the initial nucleon momentum in the laboratory frame and E the missing energy [7]. It was found that the formula…”
Section: Sidis Offmentioning
confidence: 99%
See 2 more Smart Citations
“…refs. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], for review see also refs. [19][20][21]).…”
Section: Jhep06(2016)164mentioning
confidence: 99%